Transformasi Ritual Tarea-rea Ke Bentuk Pertunjukan Randai Di Kenagarian Koto Gadang Guguk Kecamatan Gunung Talang Kabupaten Solok - Denny Regina; Darmawati Darmawati (FBS Universitas Negeri Padang, 2022)
This study aims to explain the transformation of the Tarea-rea Ritual into the form of a Randai performance in the Koto Gadang Guguk village which is still being performed now. This research uses qualitative research whit a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as cellphone cameras and stationery. The type of data used is the type of primary data and secondary data. Data collection techniques were carried out through literature study, observation, interviews and documentation. The data analysis technique used consisted of data collection, data reduction, data presentation and conclusion drawing. The result of this research is that the Ritual Transformation of Tarea-rea into Randai can be seen from the form of the performance. Tarea-rea is not only performed in the rice fields but has been performed for performances such as nagari consensus, festivals and wedding parties. The change is due to the change of mindset that has been reorganized whit new patterns and does not eliminate all the elements in the Tarea-rea ritual so that the traditions of the community do not simply become extinct and continue to develop.